PTU-204 The prevalence and significance of anaemia in patients receiving chemoradiotherapy treatment for squamous cell carcinoma of the anus. (22nd June 2015) - Bulla, R; Humes, D; Scholefield, J; Walter, CJ
Abstract : Introduction: Anaemia at disease presentation is known to be associated with worse outcomes in a number of cancers. In squamous cell carcinoma of the anus some of this effect may result from the relative radioresistance offered by anaemia-induced tumour hypoxia. 1 This study aimed to examine the relationship between pretreatment anaemia and survival in patients undergoing chemoradiotherapy treatment of squamous cell carcinoma of the anus. Method: All patients diagnosed with squamous cell carcinoma of the anus between 2005–2012 at Nottingham University Hospitals NHS Trust (NUH) were identified from the multidisciplinary team database. Retrospective data collection was undertaken using the electronic and case note records of those patients whose primary treatment was with chemoradiotherapy. The patients were divided into 2 groups: the anaemic group (Haemoglobin (Hb) <120 g/L and non-anaemic group (Hb ≥ 120 g/L). Their baseline demographics and clinical outcomes were compared. Results: Seventy-six patients (50 female and 26 male) with a median age of 63 years (IQR 52–74) were treated at NUH for squamous cell carcinoma of the anus with chemoradiotherapy over the 8-year study period. Of these 21 (28%) were anaemic at presentation, 2 of these patients received blood transfusions during their treatment but their Hbs remained below 120 g/L. There was no significant difference in follow-up times between the anaemic and non-anaemic groups with median clinical follow-up of 39 months (IQR 11–68) and 35 months (IQR 25–48) (p = 0.8) respectively. Anaemia was associated with increased mortality with a hazard ratio (HR) of 2.52 (95% CI 1.05–6.05). Multivariate analysis of mortality adjusting for the known confounders of age, sex and stage of disease demonstrated a HR of 2.06 (95% CI 0.80–5.35). Conclusion: In this study over a quarter of patients with squamous cell carcinoma of the anus were anaemic at presentation. Anaemia was associated with increased mortality. This association weakened when adjusting for stage of disease at presentation. Further research examining the role of correcting pretreatment anaemia prior to radiotherapy treatment is required in order to understand how best to optimise patient outcomes following chemoradiotherapy. Disclosure of interest: None Declared. Reference: Vaupel P, Thews O, Hoecke M. Treatment resistance of solid tumors: role of hypoxia and anaemia. Med Oncol. 2001;18:243–59